Теоретико-правові аспекти політичної реформи в Україні - Кабанець, Н.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2004)
В статье автор продолжает развивать ранее изложенные идеи об устройстве «чистой республики» с точки зрения необходимости воссоздания в процессе проведения конституционной
реформы деонтологически заданной трёхчленной структуры представительства государственно-политических интересов в форме двухпалатного парламента и президента с целью создания эффективного механизма государственной власти в украинском обществе. The note continues elaborating on ideas expressed by the author earlier with regard to “the pure republic”
in the context of the constitutional reform presently ongoing in Ukraine. The process of modeling
the reform, as viewed by the author, should take into account the necessity for “reproduction” of the deontologically pre-given three-member structure of the government of state-political interests in the form of two-chamber parliament and president for the purposes of creation an effective mechanism of the state power in the Ukrainian society.